2008
DOI: 10.1021/ol7031043
|View full text |Cite
|
Sign up to set email alerts
|

Tin-Free Giese Reaction and the Related Radical Carbonylation Using Alkyl Iodides and Cyanoborohydrides

Abstract: Tin-free Giese reaction and the related radical carbonylation process proceeded efficiently in the presence of sodium cyanoborohydride and tetrabutylammonium cyanoborohydride. The reaction took place chemoselectively at the carbon-iodine bond but not at the carbon-bromine and carbon-chlorine bonds. The iodine atom transfer followed by hydride reduction of the resulting carbon-iodine bond is proposed as a possible mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Reduction of alkyl mercurials is attended by free radical reactions of intermediate carbon radicals with molecular oxygen and free radical mechanisms have been written for the reaction of the reducing agent with alkyl halides as well. (49-52) The borohydride ion has been proposed to be a source of hydrogen atoms with the radical anion of BH 3 as a chain-propagating intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of alkyl mercurials is attended by free radical reactions of intermediate carbon radicals with molecular oxygen and free radical mechanisms have been written for the reaction of the reducing agent with alkyl halides as well. (49-52) The borohydride ion has been proposed to be a source of hydrogen atoms with the radical anion of BH 3 as a chain-propagating intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…Tin-free Giese reaction has been developed relying on this useful reactivity of CO [60]. Reaction of iodide 85 with acrylate 84 in the presence of CO (90 atm) and n-Bu 4 NBH 3 CN led to the formation of the keto ester 86 in satisfying yield (Scheme 14.20, (1)).…”
Section: Alkyl Halide Carbonylationmentioning
confidence: 99%
“…Under the reaction conditions where a catalytic amount of fluorous tin hydride and an excess amount of sodium cyanoborohydride were used, initially formed aldehydes can be converted into hydroxymethylated compounds in one-pot [79], since borohydride acts not only as the reagent for the regeneration of tin hydride [1013] but also as the reagent for aldehyde reduction. Later on we found that borohydride reagents can also serve as radical mediator delivering hydrogen to the radical centre [14], thus we developed a hydroxymethylation method using Bu 4 NBH 4 and a radical initiator [1517]. Recent work in collaboration with Dennis Curran has revealed that, with the use of NHC-borane [18], hydroxymethylation of aromatic iodides can be attained [19].…”
Section: Introductionmentioning
confidence: 99%